Fleksibility and strenght of rowers - Zuzanna Piekorz; Maciej Danielski; Katarzyna Strojek; Paweł Molski; Walery Zukow; Andrzej Lewandowski (Kazimierz Wielki University, 2018)
Introduction: The physical activity is essential for the normal functioning of the musculoskeletal system. Both deficiency and excess of motion can be harmfull. This issue mostly concern all kinds of sport players. The rowing, as a sport discipline, is physicly demanding so that activates most of human muscles. An inadequate training can lead to serious disorders of the musculoskeletal system. Demages can be caused by the nature of particular sport discipline or training loads. Aim of the thesis: The main goal is to examin and present differences in force level and flexibility factor among sportsman according to used oar. Take hypothesis that bigger inequality in strenght and flexibility have rowers of oar. Material and methodology: Research covered rowers of left and right oar and also symmetric paddle in age between 15 to 28 years old with at least 3 years training experience. From all contestants measurement of weight and height were taken. Another examined factors were range of corps movement and strenght in moves: a corps flexion forward, hyperextension of the corps, rotation into left and right and lateral flexion on the left and right side. Material was analized by normal distribution and comparison of inner group. Results of rowers were compered by groups used various rowing equipment. Results: It is said, that symmetric rowing supports steady muscle strenght development in players corpses. Other noticed issue concerning rowers using oars is possesion of bigger force for corps rotation towards hand used for rowing. It is also observed for both symmetric and asymmetric rowers that they have better strenght of corps rotation on whatever side of the body. Conclusions: Research confirms sygnificant influence of morphology on sport results but with no visible difference in used rowing tools or in force inequality of oar players and their lack of flexibility The introducion of symmetric excercises can be beneficial for athletes especially in intesive training period by decreasing risk ijury and improvement of sport achievements.